2021
DOI: 10.1002/iub.2446
|View full text |Cite
|
Sign up to set email alerts
|

The PI3K/Akt/mTORC signaling axis in head and neck squamous cell carcinoma: Possibilities for therapeutic interventions either as single agents or in combination with conventional therapies

Abstract: The latest advances in the sequencing methods in head and neck squamous cell carcinoma (HNSCC) tissues have revolutionized our understanding of the disease by taking off the veil from the most frequent genetic alterations in the components of the oncogenic pathways. Among all the identified alterations, aberrancies in the genes attributed to the phosphoinositide 3-kinases (PI3K) axis have attracted special attention as they were altered in more than 90% of the tissues isolated from HNSCC patients. In fact, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 204 publications
(411 reference statements)
0
13
0
Order By: Relevance
“…The PI3K/AKT/mTOR pathway is active in over 80% of HNSCC tumors because of EGFR activation (47%), PIK3CA mutations or amplifications (25%), PIK3R1 overexpression (2%) or PTEN mutation (6%) ( 2 , 89 ). In HNSCC with wild-type PIKCA expression, prolonged tyrosine phosphorylation of PI3K and HER3 recruitment resulted in abnormal PI3K/AKT/mTOR signaling and immune suppression, as shown by an independent kinome-wide siRNA screen.…”
Section: Pten/pi3k/akt/mtormentioning
confidence: 99%
“…The PI3K/AKT/mTOR pathway is active in over 80% of HNSCC tumors because of EGFR activation (47%), PIK3CA mutations or amplifications (25%), PIK3R1 overexpression (2%) or PTEN mutation (6%) ( 2 , 89 ). In HNSCC with wild-type PIKCA expression, prolonged tyrosine phosphorylation of PI3K and HER3 recruitment resulted in abnormal PI3K/AKT/mTOR signaling and immune suppression, as shown by an independent kinome-wide siRNA screen.…”
Section: Pten/pi3k/akt/mtormentioning
confidence: 99%
“…Studies have demonstrated that PI3K inhibitors represent a therapeutic strategy against HNSC. 53 - 55 Moreover, activation of JAK-STAT signaling contributes to cellular invasion and proliferation in HNSC. 56 , 57 This highlights the tumor aggression-associated role of LIMA1 in patients with HNSC.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that a combination of immune checkpoint inhibitors and mTOR inhibitors may be more effective. In fact, many pharmaceutical companies are conducting clinical trials of combinations of PI3K/mTOR inhibitors and immune checkpoint inhibitors [ 97 , 98 , 99 ]. mTOR is required for Th1 and Th2 effector T cell differentiation.…”
Section: Cancer Therapy By Targeting Mtormentioning
confidence: 99%